Overview of transcatheter patent ductus arteriosus closure in preterm infants. (27th February 2019) - Almeida‐Jones, Myriam; Tang, Nai Yu; Reddy, Aneela; Zahn, Evan
Abstract: Clinically significant patent ductus arteriosus (PDA) has been associated with significant morbidity in extremely low birth weight (ELBW) infants. Current management of ELBW infants with hemodynamically significant PDA includes supportive treatment, pharmacological therapy, and surgical ligation. All of these therapeutic options have their advantages and limitations. More recently, transcatheter PDA closure has been described as a viable option in this population. In this paper, we provide a comprehensive review of this emerging procedure.